Discovery of benzylthio analogs of fluconazole as potent antifungal agents. (23rd April 2018) - Motahari, Kamran; Badali, Hamid; Hashemi, Seyedeh Mahdieh; Fakhim, Hamed; Mirzaei, Hassan; Vaezi, Afsane; Shokrzadeh, Mohammad; Emami, Saeed
Aim: A new series of triazole alcohol antifungals8a–j were designed by introducing benzylthio functionality on one triazole ring of fluconazole.Results: The antifungal activity evaluation of target compounds against 16  Candida isolates indicated that all compounds with MIC values of 0.063–1 μg/ml had better profile of activity in respect to fluconazole (MICs = 0.5–4 μg/ml) against fluconazole-susceptible isolates. In particular, the representative compounds8b and8e were also active against fluconazole-resistant isolates of Candida albicans and Candida parapsilosis (MICs = 0.063–16 μg/ml). Cytotoxicity assay against Hep-G2 and NIH-3T3 cell lines revealed that these compounds can display potent antifungal activity at noncytotoxic concentrations.Conclusion: The prototype compound8b could be considered as a new lead for design and development of potent antifungal agents.